The effect of periodized resistance training on accelerative sprint performance - Moir, G.; Sanders, R.; Button, C.; Glaister, M. (Sports Biomechanics, 2007)
The purpose of this study was to assess the effect of periodized resistance training on accelerative sprint performance. Sixteen physically active men participated in a randomized controlled study. An experimental group (n = 10) completed an 8-week periodized resistance training intervention, while a control group (n = 6) did not train. Pre- and post-training measures of 20-m straight-line sprint time, including a 10-m split, maximum strength, and explosive strength, were recorded. Flight time, stance time, stride length, and stride frequency were quantified from digitized video recordings of the first three strides of the 20-m sprint. Resistance training resulted in significant increases in maximum strength (parallel back squat: 19%) and explosive strength (6-10%). However, both groups increased 0-10 m sprint times (experimental group = 6%; control group = 3%) while 10-20 m times were reduced (experimental group = 7%; control group = 4%), highlighting the mechanical differences between the distinct sprint phases. The change during the 0-10 m interval was accompanied by a reduction in stride frequency during the first three strides. Strength coaches should be aware that the potential benefits of increased muscular strength during short sprints are likely to be affected by mechanical specificity and that improvements in sprinting performance may not occur immediately after a period of resistance training.